Noun Phrases in "Imaji Terindah" Novel By Sitta Karina: A Generative Transformation Analysis - Rona Almos (Jurnal Lingua Idea, 2021)
This article is about noun phrases that basically consists of a noun. The data used in this article is taken from the novel "Imaji Terindah" by Sitta Karina with a generative transformation approach. The theory of generative transformation is a system of rules consisting of a limited set of rules but capable of generating or creating a limited number of sentences. There are three stages followed in this research method, namely the stage of providing data. In this step, the listening method is used. Then in analyzing the data analysis, the author uses the distributional method. And the last stage presenting the results of data analysis. At this stage the author uses a formal method. The characteristic of noun phrases in this novel is the noun as the main element. Noun phrases is functioned the subject, predicate, and object. Based on the characteristics of noun phrases in this novel, the elements of noun phrases are grouped into two types, namely primary elements and modifier elements. In the novel "The most beautiful image" by Sitta Karina, there are many sentences using the 'yang' relator.